Transparency and accountability in the negotiation of the US-Mexico-Canada trade agreement: the case of pharmaceuticals - Anna S Y Wong, BSc; Clarke B Cole, MSc; Jillian C Kohler, PhD (Elsevier, 2021)
Background: Transparency and accountability are essential components at all stages of the trade negotiation process. This study reports on the findings of an evaluation of the United States' public consultation process during the re-negotiation of the North American Free Trade Agreement (NAFTA)/United States-Mexico-Canada Agreement (USMCA) with respect to medicines and the pharmaceutical sector. Methods: A desk review was conducted to map the US negotiation rounds of the USMCA. Then, opportunities for the public to receive information and provide feedback about the proposed agreement provisions were identified. Finally, the written comments submitted by stakeholders during this public consultation process to the Federal Register (Regulations.gov) were queried and analysed using qualitative data analysis software NVivo for language related to pharmaceuticals and medicine. Findings: The public consultation process occurred before the start of official negotiations. It was overseen by the Office of the US Trade Representative (USTR) and included both written comments and oral testimony about US negotiation objectives. There were no further official opportunities for the public to engage with the negotiation process. Of the 1458 comments publicly available through the Federal Register, 75 specifically discussed issues related to pharmaceuticals for human use. More than 50% of submissions received from members or affiliates of the pharmaceutical industry advocated for strengthened pharmaceutical intellectual property rights, greater regulatory data protection, or both. Nearly all submissions from non-industry groups indicated that access to, or the affordability of, medicines was a priority issue area in the renegotiated agreement. Most submissions that directly discussed transparency and accountability were authored by industry groups and emphasised the importance of predictability and transparency in the areas of pharmaceutical intellectual property, regulatory affairs, pricing, and reimbursement to facilitate greater innovation. Interpretation: USMCA increased regulatory data protection for innovator drugs, increased the period of regulatory exclusivity for biologics, and granted patent term restoration provisions for regulatory delays, undermining public access to medicines. Although industry comments only constitute 26% of the comments submitted during the US public consultation period related to pharmaceuticals, they reflect the dominant position adopted in the USMCA. Funding: Connaught Fund Global Health Challenge Award.